1998
DOI: 10.1038/sj.onc.1202115
|View full text |Cite
|
Sign up to set email alerts
|

The Tek/Tie2 receptor signals through a novel Dok-related docking protein, Dok-R

Abstract: Tek/Tie2 is an endothelial cell-speci®c receptor tyrosine kinase that has been shown to play a role in vascular development of the mouse. Targeted mutagenesis of both Tek and its agonistic ligand, Angiopoietin-1, result in embryonic lethality, demonstrating that the signal transduction pathway(s) mediated by this receptor are crucial for normal embryonic development. In an attempt to identify downstream signaling partners of the Tek receptor, we have used the yeast two-hybrid system to identify phosphotyrosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 48 publications
7
140
2
Order By: Relevance
“…Lee et al (2008) previously showed an increase in the number of bone marrow cell colonies derived from irradiated mice under Ang-1 treatment. It was also notified that exogenous Ang-1 could preserve the mix feature colony-forming capacity of hematopoietic stem cells by the Ang-1/Tie-2 signaling pathway (Arai et al 2004;Jones and Dumont, 1998). Corroborating to our results, Ang-1 initiated EPC to EC maturation by the upregulation of CD31 and subsequent high capacity of Ac-LDL uptake.…”
Section: Discussionsupporting
confidence: 59%
“…Lee et al (2008) previously showed an increase in the number of bone marrow cell colonies derived from irradiated mice under Ang-1 treatment. It was also notified that exogenous Ang-1 could preserve the mix feature colony-forming capacity of hematopoietic stem cells by the Ang-1/Tie-2 signaling pathway (Arai et al 2004;Jones and Dumont, 1998). Corroborating to our results, Ang-1 initiated EPC to EC maturation by the upregulation of CD31 and subsequent high capacity of Ac-LDL uptake.…”
Section: Discussionsupporting
confidence: 59%
“…The sequences of DOK1/2 in human and Dok1/2/3 in mice have been reported previously. 3,7,[11][12][13]15,16 Recently, Dok4/5 genes have been cloned from mouse tissues. 21 The amino acid sequences from human DOK3/4/5 genes have been deduced (see Material and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…3,[6][7][8] The structure of Dok-1 presents some similarities with other adapter molecules such as Gab proteins or insulin receptor substrate (IRS) proteins. 9,10 Two proteins sharing extensive sequence homology with the amino-terminal part (PH and PTB domains) of Dok-1 have been cloned: Dok-2 (also known as FRIP or Dok-R) [11][12][13][14] and Dok-3 (also known as Dok-L). 15,16 These proteins are essentially expressed in hematopoietic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…downstream activation of p125FAK. 30 In addition, it has been reported that phosphorylation of Y1106 on the Tie2 receptor recruits the Tie2-associated docking molecule Dok-R. 12 Recruitment of Dok-R to activated Tie2 leads to its phosphorylation and subsequent recruitment of Nckp21 activated kinase (Pak) complex to the membrane. 14 Release of endothelium-derived NO requires the activation of eNOS, which until recently has been thought to be largely regulated by a Ca 2ϩ and calmodulin.…”
Section: Tie2 Signal Transductionmentioning
confidence: 99%
“…1,5 In vitro experiments have shown that Ang1 induces endothelial cell (EC) sprouting in vitro, 6,7 and stimulates EC migration 8 and the formation and stabilization of capillary-like networks in culture systems. 9 -11 One of the signaling cascades initiated by Tie2 phosphorylation is the recruitment of Dok-R, 12 a novel docking molecule that on phosphorylation binds to proteins containing Src homology 2 (SH2) domains. 13 The recruitment of a Nck-p21 activated kinase (Pak) complex to Dok-R, 14 mediates EC migration.…”
mentioning
confidence: 99%